Pengaruh Pengeluaran Pemerintah dan Laju Inflasi Terhadap Pertumbuhan Ekonomi di Aceh - Shinta Liana Fitri; Puti Andiny; Yani Rizal; Safuridar Safuridar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Economic growth in Aceh Province is an important issue that shows regional development through the increase in goods and services produced. Based on data from the Central Statistics Agency (BPS), Aceh's economic growth only reached an average of 3.88% in 2018, far below the national average of 5.01%, which reflects challenges in resource utilization. Inflation in Aceh has experienced significant fluctuations between 1.53% and 8.09% from 2019 to 2023, which has the potential to hinder economic growth. Government expenditure also plays a crucial role in driving growth, where during the 2019-2023 period, the average development budget reached Rp 12.96 trillion, but the budget realization was only around Rp 12.29 trillion. This shows that despite large expenditures, the impact on economic growth has not been significant. In the theory of economic growth, there are various views on the factors that affect growth. Classical theory emphasizes the role of capital, labor, and technology, while Schumpeter's theory highlights innovation as the main key to growth. Inflation can serve as a barrier or driver, depending on economic conditions, while government spending is expected to stimulate economic growth through an increase in aggregate demand. This study uses inferential statistics to analyze the influence of inflation and government spending on Aceh's economic growth during the 2015-2023 period. The results of the analysis show that government spending has a positive and significant influence on economic growth, while inflation does not show a significant influence.